The Effect of Outsourcing on Financial Performance on an Organisation - Christine Nyadoi (Uganda Christian University, 2023)
The study looked into how Mukwano Industries' financial performance was affected by outsourcing. It especially examined the connection between outsourcing and Mukwano Industries' financial performance; the different types of outsourcing that improve Mukwano Industries' financial performance, and the effects of out sourcing on Mukwano Industries' financial performance. A case study methodology and a quantitative approach were used in the investigation. 50 respondents made up the study's target group, while 40 respondents were chosen at random for the sample size. The sample was chosen using both intentional and accidental sampling methods. As the main sources for data, primary and secondary sources were investigated. The study's instruments for collecting data included the questionnaire. The researcher then used SPSS to evaluate the data and create frequency tables on which the data was displayed. According to the results of objective 1, adequate competency of the external service provider improves financial performance. The results of goal two revealed that multiple supplier outsourcing improves financial performance since it guarantees that the candidate hired for a position genuinely understands what to do, which boosts financial performance. According to the findings of goal three, Mukwano Industries' financial performance has been severely harmed by the lack of transparency in outsourcing. It was found that better external service provider capacity boosts financial performance. The study came to the conclusion that outsourcing to multiple suppliers improves financial performance. It was ultimately determined that Mukwano Industries' financial performance had been negatively impacted by outsourcing's lack of transparency. It was advised that Mukwano Industries' management implement efficient outsourcing to lower the cost of routinely supervising new outsourced partners and boost the company's financial performance. It was underlined that the university administration should host forums and businessperson conversations before teaching businesspeople better outsourcing tactics to boost their financial success.
This is a dissertation.